Contributions of Intracellular Ions to Kv Channel Voltage Sensor Dynamics - Goodchild, Samuel; Fedida, David (Frontiers in Pharmacology, 2012)
Voltage sensing domains of Kv channels control ionic conductance through coupling of the movement of charged residues in the S4 segment to conformational changes at the cytoplasmic region of the pore domain, that allow K+ ions to flow. Conformational transitions within the voltage sensing domain caused by changes in the applied voltage across the membrane field are coupled to the conducting pore region and the gating of ionic conductance. However, several other factors not directly linked to the voltage dependent movement of charged residues within the voltage sensor impact the dynamics of the voltage sensor, such as inactivation, ionic conductance, intracellular ion identity and block of the channel by intracellular ligands. The effect of intracellular ions on voltage sensor dynamics is of importance in the interpretation of gating current measurements and the physiology of pore/voltage sensor coupling. There is a significant amount of variability in the reported kinetics of voltage sensor deactivation kinetics of Kv channels attributed to different mechanisms such as open state stabilization, immobilization and relaxation processes of the voltage sensor. Here we separate these factors and focus on the causal role that intracellular ions can play in allosterically modulating the dynamics of Kv voltage sensor deactivation kinetics. These considerations are of critical importance in understanding the molecular determinants of the complete channel gating cycle from activation to deactivation.